Cochlospermum regium (Mart. ex Schrank) Pilg.: Evaluation of chemical profile, gastroprotective activity and mechanism of action of hydroethanolic extract of its xylopodium in acute and chronic experimental models. (6th April 2019) - Arunachalam, Karuppusamy; Damazo, Amilcar Sabino; Pavan, Eduarda; Oliveira, Darley Maria; Figueiredo, Fabiana de Freitas; Machado, Marco Tulio Marra; Balogun, Sikiru Olaitan; Soares, Ilsamar Mendes; Barbosa, Robson dos Santos; Alvim, Tarso da Costa; Ascêncio, Sérgio Donizeti; Martins, Domingos Tabajara de Oliveira
Abstract: Ethnopharmacological relevance: Cochlospermum regium (Bixaceae) is a native shrub of Brazil and its xylopodium (infusion/decoction) is being used for the treatment of gastritis, ulcers, arthritis, intestinal infections, gynaecological infections, skin diseases, among others. The aim of the present study was to evaluate the gastroprotective/antiulcer activity and the mechanism of action of hydroethanolic extract of C. regium xylopodium (HECr), using in vitro and in vivo models. Additionally, phytochemical constituents were identified by high-performance liquid chromatography (HPLC). Materials and methods: C. regium xylopodium was macerated with ethanol/water to obtain the HECr. The phytochemical characterisation was carried out by HPLC. The antiulcer efficacy of HECr (25, 100 and 400 mg/kg, p.o.) was evaluated using acute acidified ethanol (HCl/EtOH), piroxicam and water immersion-induced experimental ulcer models. Chronic gastric ulcer healing activity of HECr was evaluated through acetic acid (99.8%) – induced model. Histological analysis and myeloperoxidase (MPO), glutathione (GSH), catalase (CAT) activities were also evaluated in chronic ulcer induced gastric tissues. The plausible mode of action of the HECr was assessed by estimation of gastric wall mucus production and the role of gastric secretion in pylorus ligature. The animals were also pre-treated with various inhibitors which includes indomethacin (10 mg/kg, p.o.) a selective inhibitor of cyclooxygenase, L-NAME (10 mg/kg, i.p.), an inhibitor of nitric oxide synthase, glibenclamide, a ATP-sensitive potassium channels (K + ATP ) blocker (5 mg/kg, p.o.) or yohimbine (2 mg/kg, i.p.), an α2 -adrenergic receptor antagonist. In vitro, Helicobacter pylori action was done by broth microdilution method. Results: The HPLC analysis data revealed the presence of gallic acid, rutin, myricetin, morin and kaempferol. HECr promoted protective effect against acute ulcers induced by HCl/EtOH with inhibitions of 47.52% ( p <  0.01) and 62.69% ( p <  0.001) at 100 and 400 mg/kg, and in piroxicam by 34.11% ( p <  0.05), 49.14% ( p <  0.01) and 61.34% ( p <  0.001), at 25, 100 or 400 mg/kg, respectively, and in water restraint stress by 78.26% inhibition, p <  0.001, at the dose of 400 mg/kg when compared to the vehicle control group respectively. In the chronic gastric ulcer model, HECr (25, 100 and 400 mg/kg p.o.) significantly ( p  < 0.001) decreased the injured area by 58.80%, 77.87% and 71.10% respectively. Histological examination indicated that oral treatment of HECr promoted healing of gastric lesions by regenerating gastric mucosa layer with less inflammatory cells. HECr augmented the GSH, CAT activities and reduced MPO level. The pre-treatment with HECr increased the gastric wall mucus production. It also significantly altered the gastric secretion parameters by causing the reduction in the gastric juice volume, elevated the pH level and reduced the total acidity at all doses tested when compared with the vehicle group. HECr at the most active dose (100 mg/kg) reversed completely the reduction of PGs, NO production, closure of K + ATP - channels and α2 -adrenoreceptor blockage – induced damages. In microdilution assay, the HECr showed good anti- Helicobacter pylori effect with MIC = 100 µg/mL. Conclusion: The HECr presented preventive and curative effects in the experimental gastric ulcer models, besides good anti- Helicobacter pylori activity, which supports the traditional medicinal use of the xylopodium of this plant for gastrointestinal diseases. The underlying mechanisms of this antiulcerogenic/antiulcer action involve, at least, augmentation of mucus production, inhibition of gastric secretion, stimulation of PGs and NO synthesis. And that it involves activation of K + ATP channels and α-2-adrenergic receptors, in addition to an antioxidant activity, probably due to the presence of gallic acid and flavonoids in HECr. Graphical abstract: fx1